Leadership Character Employed in Islamic Education Perspective Based on Al-Qur'an Surah Yusuf - Rudian Putra Pulungan; Zulheddi Zulheddi; Mohammad Al Farabi (Jurnal Basicedu, 2022)
This study aims to analyze the character of leadership in Islamic education from the perspective of the Qur'an Surah Yusuf as an effort to set an example for children. This is based on the uswah exemplified by the Prophet Yusuf towards his followers with a reflection of noble character. This research belongs to the category of qualitative research with a literature study method. Research materials or data are sourced from interpretations and relevant scientific literature, then the data is analyzed by trying to describe leadership objectively about the interpretation of Surah Yusuf from the contents of the book Tafsir al-Munir by Wahbah az-Zuhaili and Tafsir Al-Azhar by H. Abdul Malik Karim Amrullah. (Hamka), then the researcher analyzed it in depth. Based on the results of literature research, the criteria for leaders in Islamic education QS Yusuf are honest, patient, love the homeland, fair, trustworthy, responsible, and knowledgeable. Based on this, it will be known how the leaders influence the people they lead. These influences include: influencing behavior that evokes emotions and strong identification of followers towards the leader, being able to easily mobilize elements of subordinate leadership to fully serve the interests of the community, leaders will be judged by the community as having extraordinary abilities and determining factors. so that state affairs will be easily resolved by being oriented towards dynamic change. Through this research, it was found the concept of efforts to give an example to children with uswah leadership of the prophet Yusuf a.s.